A bride's story. 10 - Mori, Kaoru, 1978- (Yen Press, 2018)
Acclaimed creator Kaoru Mori's tale of life on the nineteenth-century Silk Road continues. Karluk has left home to become a man! For four months, he's off to learn falconry from Amir's brothers, living with them at their winter camp. As his training commences, what will Karluk learn about himself, and Amir, in the process?